INVESTIGATING THE IMPACT OF CONTINUOUS PROFESSIONAL DEVELOPMENT ON THE PERFORMANCE AND JOB SATISFACTION OF LABORATORY TECHNICIANS AND SPECIALISTS - Faisal Falah Th Aldhafeeri, Faisal Naif Shalan Aldhafeeri , Samiyah Sayyab Abdullah Aldhafeeri, Norah Molfi G Alenezi, Specialist, Ashjan Nasser Hulayyil Aldhafeeri, Ahmad Khamees A Aldhafeeri (Chelonian Research Foundation, 2022)
Continuous professional development (CPD) plays a crucial role in maintaining and enhancing the knowledge, skills, and competencies of healthcare professionals. This study aims to investigate the impact of CPD on the performance and job satisfaction of laboratory technicians and specialists. A mixed-methods approach was employed, involving a survey questionnaire and semi-structured interviews. The findings reveal that regular participation in CPD activities significantly improves job performance, increases job satisfaction, and promotes a positive work environment. However, challenges such as time constraints and limited resources were identified as barriers to effective CPD implementation. The study highlights the need for healthcare organizations to prioritize CPD and provide adequate support to their laboratory staff to ensure optimal patient care and employee well-being. Keywords: Continuous professional development, laboratory technicians, laboratory specialists, job performance, job satisfaction